Four Museums + A Monument (Oz, 1989)
Work by fifth-year students in the Kansas City Academic Program In 1921 Kansas City held a national design competition to produce a design for a memorial to those who fought in World War I. Harold van Buren Magonigle's prize-winning entry contained...